(untitled) (Indus Journal of Bioscience Research, 2025)
Background: Mesh hernioplasty remains an effective surgery for the treatment of abdominal wall hernias. However, postoperative mesh infection is a common complication that ranges from 5- 10%. Management in conventional medicine entails mesh removal, which exposes the patients to such things as incisional hernias and technical difficulties at the time of mesh removal. Methodology: This cross-sectional retrospective medical record review was performed at the department of General Surgery, Recep Tayyip Erdogan Hospital, Muzaffargarh. After approval from the Institutional Review Board, approval number IHHN_IRB_2023_05_005, the computerized medical records of all the patients (any gender, any age) presenting with SSI after any type of mesh repair for any type of hernia done from January 2015 to March 2023 were reviewed. The data were entered into the computer and analyzed by using software IBM SPSS Statistics 26. Results: Of the 22 documented SSI patients, 19 cases (86.4%) were treated conservatively without mesh removal, while only one patient required mesh removal. Conclusion: This expanded case-control analysis examines the outcomes of conservative treatment for the infected mesh, which may entail antibiotics, drainage, debridement, and NPWT. The findings also confirm that it is possible to salvage most of the meshes to minimize surgical risks, resulting in better outcomes for the patients. Whenever feasible and particularly in situations with known intraocular penetration or Worthington degree III or IV exposure, removal of the foreign body should not be considered unless conservative management fails.